TRANSFORMATIVE PAI LEARNING ORIENTED TOWARD ENVIRONMENTAL ETHICS AND ANTI-BULLYING: AN ANALYSIS OF TEACHERS’ STRATEGIC ROLES AND INSTRUCTIONAL METHODS - Junaidi Junaidi; Abdul Muis; Moh. Nawafil; Wedi Samsudi; Muhammad Sulaiman (UIN Antasari Banjarmasin, 2026)
Abstract : The escalating prevalence of bullying has generated severe consequences for students’ mental health and the overall school climate, necessitating innovative pedagogical designs capable of mitigating such phenomena. Concurrently, the ongoing ecological crisis presents a critical challenge for educators to cultivate environmental ethical awareness through value-oriented learning processes. This study aims to examine the role of Islamic Religious Education (PAI) teachers and the implementation of transformative learning approaches oriented toward environmental ethics and anti-bullying. Employing a qualitative design, data were collected through in-depth interviews, participant observations, and document analysis. The findings reveal that the effectiveness of PAI learning in this context is significantly influenced by the strategic role of teachers and the pedagogical methods employed. Teachers’ roles encompass instructional planning, exemplary conduct, and the facilitation of students’ social-emotional development. Furthermore, dialogic and problem-based learning approaches have been demonstrated to enhance ethical awareness, active engagement, and critical thinking skills among students. This study contributes to the development of a transformative PAI learning model that addresses contemporary social challenges and offers practical implications for fostering environmentally responsible and anti-bullying educational environments. Keywords : PAI; Ecological Crisis; Bullying; Teachers Role;